Microgreen: A tiny plant with superfood potential - Mahinder Partap; Diksha Sharma; Deekshith HN; Meenakshi Thakur; Vipasha Verma; Ujala; Bhavya Bhargava (Journal of Functional Foods, 2023)
The design of novel and functional foods is a major driver of innovation in the food industry, which strives to meet consumer's rising demand and expectations for healthy foods. In recent years, microgreens have received popularity as functional foods due to their high-density nutrients and bioactive or secondary metabolite content. The morphology of microgreens is comprised of well-developed cotyledonalary leaves, immature true leaves, and a central stem. The scientific literature has documented numerous studies on microgreens such as nutritional content assessment, metabolite accumulation, nutraceutical potential, and shelf life enhancement. Physical, chemical, biological, and cultivation factors significantly increased the microgreen’s photosynthetic efficiency, growth, nutrient profile, antioxidant activity, and metabolite content. Using omics data, scientists have investigated the underlying molecular mechanism and potential gene(s) associated with nutrients, specialized metabolites, stress resistance, shelf-life enhancement, and disease resistance in nutraceutical plants.